Analysis of Citizen Relations Management (CRM) Service Quality Application in Waste Handling at Balekambang Sub District, Kramat Jati, East Jakarta - Yulianto, Yulianto; Ambarsari, Retno (Technium Social Sciences Journal, 2022)
The DKI Jakarta Provincial Government in carrying out government issues policies by utilizing information and communication technology to solve city problems quickly and precisely. The DKI Jakarta Provincial Government in capturing the problems of its citizens has 14 official complaint channels whose handling is integrated in the Citizen Relations Management (CRM) application, based on the dimensions that affect service quality, namely the Tangible, Reliability, Responsiveness, Assurance and Empathy dimensions. This study uses a qualitative method with a descriptive approach. Data was collected by means of interviews, observation, and documentation. Data analysis used three components consisting of data reduction, data presentation and conclusion drawing. Test the validity of the data by testing the criteria for credibility, transferability, dependability and comformability. The results of the research on the service quality of CRM applications in handling waste in the Balekambang village in terms of five dimensions of service quality, namely tangible, responsiveness and assurance dimensions are good, while the reliability dimension still requires increasing the knowledge and performance of officers in the field as well as the empathy dimension is not fully in line with expectations, because there are still officers who feel emotional when following up on reports. Lack of public understanding and knowledge about CRM applications, facilities and infrastructure as well as geographical conditions are factors that hinder the quality of CRM application services, while the implementation of CRM application socialisation to the RT/RW level is a supporting factor for CRM application service quality.